2018
DOI: 10.2478/logi-2018-0020
|View full text |Cite
|
Sign up to set email alerts
|

Promoting the Use of Social Commerce on SME in the Context of Logistics: UTAUT Model Examination

Abstract: Small and Medium Enterprises (SME‟s) was proven to increase the country economic condition due to its capability to retain the product and capital flow stay inside. SME‟s tend to be more creative than the large and traditional enterprises, though the profitability may vary across segment. The rise of technology has brought the customer to be more educated related to product due the ease of information dissemination. Web 2.0 was the basic of today’s social media communication in the context of logistics, enabli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
3
5
0
Order By: Relevance
“…As shown in Figure 2, the UTAUT model consists of four main constructs that predict the intention to adopt an IS-performance expectancy, effort expectancy, social influence, and facilitating conditions. While the technology acceptance model (TAM) was proven to have about 40% of the explanatory power, when its validity was tested in the business sector, including for logistics [2] and supply chain management (SCM) [14], the UTAUT model's explanatory power improved to about 70%, in addition to providing multiple predictors [13]. Thus, the UTAUT is more widely used when validating the intention to adopt logistics systems, application programs (e.g., SCM), and new information technologies [15,16].…”
Section: Utautmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure 2, the UTAUT model consists of four main constructs that predict the intention to adopt an IS-performance expectancy, effort expectancy, social influence, and facilitating conditions. While the technology acceptance model (TAM) was proven to have about 40% of the explanatory power, when its validity was tested in the business sector, including for logistics [2] and supply chain management (SCM) [14], the UTAUT model's explanatory power improved to about 70%, in addition to providing multiple predictors [13]. Thus, the UTAUT is more widely used when validating the intention to adopt logistics systems, application programs (e.g., SCM), and new information technologies [15,16].…”
Section: Utautmentioning
confidence: 99%
“…Many studies have identified UTAUT constructs as factors that positively affect the attitude and the sustainable usage intention of information system [2]. Hence, UTAUT constructs as independent variables have strong explanatory power over the dependent variable.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] Eventhough Small and Medium Enterprises (SME"s) was proven to increase the country's economic condition due to its capability to retain the product and capital flow stay inside. [3] but the reduction in merchant income is able to decreace the country's economic condition…”
Section: The Income Of Traders Before and After Being Affected By Covid-19mentioning
confidence: 99%
“…SME's tend to be more creative than large and traditional enterprises, though the profitability may vary across the segment. [3] Amid COVID-19, direct sales generally have decreased due to the pattern of people staying more at home. Many SMEs also choose not to open shops because of the operational hours restrictions or the imposition of Large-Scale Social Restrictions (PSBB) in several areas of E-commerce sales.…”
Section: Introductionmentioning
confidence: 99%